Foldon fusion of RBD and S1 fragments of SARS‐CoV‐2 to stabilize the structure of subunit protein as a vaccine candidate - Gracia Christine Lembong Purwanto; Fedric Intan Damai; Dian Fitria Agustiyanti; Popi Hadi Wisnuwardhani; Alfi Taufik Fathurahman; Yana Rubiyana; Ratna Dwi Ramadani; Muhammad Khairul Lisan Sidqi; Pekik Wiji Prasetyaningrum; Endah Puji Septisetyani; Dadang Supriatna; Ratih Asmana Ningrum; Wien Kusharyoto; Ihsan Tria Pramanda; Andri Wardiana (Universitas Gadjah Mada, 2023)
The COVID‐19 pandemic threatened public health around the world at the same time as highlighting the urgency of vaccine development. Subunit vaccines are safe and effective vaccine types that utilize parts of viruses to trigger the body’s immune response. Previous research has shown that fusion of the spike protein with the foldon domain (fd) achieved the trimeric form to increase the protein stability of the recombinant subunit protein spike from SARS‐CoV and MERS‐CoV, thus exceeding the immune response in the body. The study aims to observe the expression of RBD‐fd and S1‐fd recombinant proteins from the spike protein of SARS‐CoV‐2 in CHO‐K1 mammalian cells and investigate the binding activity of those proteins with hACE2 receptor, expressed in HEK293T cells using immunofluorescence staining. The plasmids were transiently transfected into the cells, followed by antibiotic selection using G418 as an initial stage to select the positive stable transformants. Protein expression was confirmed by Western blotting and showed an estimated size for monomeric RBD‐fd of 35 kDa and S1‐fd of 55 kDa. However, the trimeric form of the proteins was not observed. In addition, immunofluorescence staining showed the binding activity between the RBD‐fd and S1‐fd proteins and hACE2 expressing cell line, revealing binding and an internalization process.